Analisis Komparasi Keuntungan Usahatani Padi Sawah dan Bawang Putih Lokal di Subak Aya Desa Babahan, Kecamatan Penebel, Kabupaten Tabanan - KALYANADEWI, GUSTI AYU PUTU; SUAMBA, I KETUT; ARTINI, NI WAYAN PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Comparative Analysis of Farming Profits for Rice and Local Garlic in Subak Aya, Babahan Village, Penebel District, Tabanan Regency. Subak Aya is a subak in Tabanan Regency where in the same growing season some farmers plant garlic and some grow rice. The purpose of the study was to analyze the characteristics of rice and local garlic farmers and to analyze the comparative advantage of farming between rice and local garlic. The analysis uses the average difference test with the help of the SPSS application. The results of this study indicate 1) Most of the farmers who grow rice and local garlic are of productive age, namely 15-64 years with more than 10 years of farming experience with land status mostly being cultivated land and arable land area above 30 acres. The education level of most farmers is high school and the number of family dependents of most local garlic farmers is 3 people while rice farmers are more than 3 people. 2) There is a significant difference in the profits obtained by farmers of rice and local garlic (h1 is accepted), where the profit of local garlic is higher, namely Rp. 13.272.710 /ha/growing season while rice only Rp 2.111.876 /ha/growing season. Farmers are advised to maximize the production of garlic to see that the profits obtained are greater than the benefits of rice production. The role of the government is also deemed necessary to assist farmers in the form of capital (money), technology and other production facilities, so that farmers can produce garlic effectively and efficiently, increase productivity which in turn has higher competitiveness compared to the imported garlic market.